Insights into a rapid access angina clinic (RAAC): are we capturing the right cohort of patients? - Kumail Abbas Dewji; Erica Zhang; Taqiyah Nusrat; Asgher Champsi; Nadia Sunni (Future Healthcare Journal)
Introduction: The rapid access angina clinic (RAAC) is a service provided to fast-track patients with cardiac symptoms for specialist assessment.1,2 Our study aimed to assess the characteristics and presenting symptoms of patients referred to RAAC and the proportion of referrals who necessitated investigation and management that could not have been implemented outside of secondary care.  We aimed to compare these patients to those who did not yield positive findings following RAAC assessment, with a view to streamlining the referral process. Materials and methods: We conducted a retrospective observational study evaluating the characteristics of patients seen in RAAC from June to August 2024. Data collection included baseline patient characteristics (age, gender, co-morbidities and cardiac risk factors; Table 1), as well as outcomes of the assessment, such as investigations and treatments (Table 2). Descriptive statistics were used to summarise the data. Patients were grouped based on the final diagnosis into cardiac and non-cardiac. The cardiac group was further subdivided into those with significant findings requiring invasive procedures vs those only requiring medical management or surveillance.   Results and discussion: 145 patients were assessed in the RAAC. The most common presenting symptom was chest pain (48%), followed by shortness of breath (32%) and palpitations (30%). The most common investigation performed was transthoracic echocardiography. 53 patients had coronary assessments via imaging and functional tests. 74 patients (51%) had non-cardiac diagnoses. 46% had cardiac diagnoses, from which only 10% had significant findings requiring cardiac interventions. 36% were managed with medication and surveillance. Duplicate reviews were identified in 17 patients (12%), which highlights a potential area for scrutiny.Of those with positive findings, 40 patients were diagnosed with arrhythmias/ectopics, heart failure or primary hypertension. This suggests the need for specific hot clinics for arrhythmias and heart failure. None of the patients referred for high blood pressure were found to have secondary causes. We suggest that hypertension screens should be performed in general practice where possible or referred to general medicine.Patients who were deemed to have a cardiac diagnosis and, hence, required surveillance, medical or interventional management, were significantly older compared to the non-cardiac diagnosis cohort (median age 71 vs 51, p <0.001), were more likely to be male and to have diabetes, hypertension and peripheral vascular disease. Conversely, those with non-cardiac diagnosis had a higher prevalence of smoking and hyperlipidaemia, which indicates that referrals were appropriately made as per cardiac risk factors. Conclusion: Our audit highlighted the characteristics of patients typically seen in a RAAC clinic. With more than half of the referrals being non-cardiac and a significant amount with non-significant cardiac disease, it remains a challenge to capture the right cohort of patients. Aside from conventional cardiac risk factors, there must be a further level of stratification; this might include validated strategies, such as QRISK3 scores or stricter criteria for referral based on presenting complaint. We intend to explore this further in our next phase of work.